LEARN TO DANCE THROUGH ICE BREAKING GAMES - putri khairunnisa; Heny Rohayani; Ria Sabaria (Universitas Pendidikan Indonesia, 2022)
This research is motivated by the lack of motivation, enthusiasm, and interest in students' learning in dance lessons at school. This is allegedly due to the teacher's learning style factor which is fairly monotonous and boring so that it affects learning outcomes that are less than optimal. The purpose of this study was to describe the process and results of dance learning through Ice Breaking in class VII students at SMPN 10 Bandung. The use of Ice Breaking in dance learning activities can foster a pleasant learning atmosphere for students so that they have the desire to learn dance. This study uses a descriptive method with a qualitative approach. Collecting research data using observation, interviews and documentation studies. The subjects of the study were seventh grade junior high school students consisting of 31 students. The results of this study indicate that the Ice Breaking game can create a fun learning atmosphere. In addition, through the Ice Breaking game, it can be seen that there is a development of student learning outcomes in dance learning through increasing student grades from each meeting, so this study concludes that the use of Ice Breaking by teachers has a positive influence and impact on the process and results of dance learning for seventh grade students at SMPN 10 Bandung. This research is expected to provide benefits for readers in general, and especially for teachers in developing the dance learning process creatively and innovatively so that the learning that takes place can be interesting and fun.